Leadership of school personnel Under the Sisaket Yasothon Secondary Education Service Area Office. - Boonchuay, Jaruwan; วงษ์วัฒน์เกษม วิรัลพัชร; Romsri, Suwattanapong (Journal of Research and Development Institute Rajabhat Maha Sarakham University, 2022)
The study aims to study and compare the opinion levels of personnel towards the leadership of personnel in schools under the Sisaket Yasothon Secondary Educational Service Area Office. Classified by gender, school size and work experience The population is school personnel under the Sisaket, Yasothon Secondary Education Service Area Office. Academic Year 2020, with a sample of 344 people. research instrument as a questionnaire, it was characterized as a 5-level estimation scale with a reliability of 0.90. Data analysis to analyzed by frequency, percentage, mean, standard deviation, and the statistics used for hypothesis testing were t-test and F-test. The results shows that 1. The opinions of personnel regarding the leadership of school personnel under the Sisaket Yasothon Secondary Education Service Area Office, were at a high level. When considering each aspect, it was found that Personnel Leadership At a high level in every item. The averages were arranged in descending order, Communication skills. Creative skills. Vision Skills. Collaborative Skills respectively. 2. The opinions of personnel about the leadership of school personnel Under the Sisaket Yasothon Secondary Educational Service Area Office, classified by gender, overall and each aspect were significantly different at the .05 level, classified by school size. Overall and each aspect is no different. Classified by work experience overall is no different.